Nrf2 Is Crucial to Graft Survival in a Rodent Model of Heart Transplantation. (28th February 2013) - Wu, Wei; Qiu, Quan; Wang, Huihui; Whitman, Samantha A.; Fang, Deyu; Lian, Fangru; Zhang, Donna D.
Abstract : Currently, the sole treatment option for patients with heart failure is transplantation. The battle of prolonging graft survival and modulating innate and adaptive immune responses is still being waged in the clinic and in research labs. The transcription factor Nrf2 controls major cell survival pathways and is central to moderating inflammation and immune responses. In this study the effect of Nrf2 levels in host recipient C57BL/6 mice on Balb/c allogeneic graft survival was examined. Importantly, Nrf2 −/− recipient mice could not support the graft for longer than 7.5 days on average, whereas activation of Nrf2 by sulforaphane in Nrf2 +/+ hosts prolonged graft survival to 13 days. Several immune cells in the spleen of recipient mice were unchanged; however, CD11b + macrophages were significantly increased in Nrf2 −/− mice. In addition, IL-17 mRNA levels were elevated in grafts transplanted into Nrf2 −/− mice. Although Nrf2 appears to play a crucial role in graft survival, the exact mechanism is yet to be fully understood.